New insight in immunotherapy and combine therapy in colorectal cancer - Ji, Kai; Jia, Hang; Liu, Zixuan; Yu, Guanyu; Wen, Rongbo; Zhang, Tianshuai; Peng, Zhiying; Man, Wenjiang; Tian, Yucheng; Wang, Can; Ling, Qianlong; Zhang, Wei; et al. (Frontiers in Cell and Developmental Biology, 2025)
The advent of immune checkpoint inhibitors (ICIs) in colorectal cancer (CRC) treatment marks a major breakthrough. These therapies have proven safer and more effective than traditional radiotherapy and targeted treatments. Immunotherapies like pembrolizumab, nivolumab, and ipilimumab have pioneered new treatment avenues, potentially improving patient outcomes and quality of life. Additionally, advances in immunotherapy have prompted detailed research into CRC therapies, especially those integrating ICIs with conventional treatments, providing new hope for patients and shaping future research and practice. This review delves into the mechanisms of various ICIs and evaluates their therapeutic potential when combined with radiotherapy, chemotherapy, and targeted therapies in clinical settings. It also sheds light on the current application and research involving ICIs in CRC treatment.